The Routledge handbook on crisis, polycrisis, and public administration - Moloney, Kim (Routledge, 2025)
"This volume considers how local, national, and global crises with differing durations, sizes, and impacts challenge the public sector to respond. Within the public administration and policy disciplines, there has been limited recognition about the nature of, linkages among, and the response options for crises and poly-crises, when more than one crisis, emergency, disaster, or catastrophe (whether human-caused or natural) simultaneously impacts citizens in one geographical location. This handbook gathers experts from different fields to explore how each crisis challenges human capacity, information technology, and communication capabilities, and how public leaders must respond. These expert contributions are grouped within five thematic sections. First, Structures in Crisis: A North-South Dialogue, to engage national and global perspectives on how political, social, and economic structures respond during crises. Second, Agents in Crisis: A Cross-Actor Dialogue, on how agents respond to crises. Third, Human Capital and Information Technology in Crisis, exploring how these resources interact during crises. Fourth, Public Sector Communication in Crisis, examining issues of government and governance in effective crisis communication. Fifth, Practitioners in Crisis, a reminder to the discipline that important context and realities are missed if practitioner realities are overlooked. Chapters in the book engage twenty-three countries and one overseas dependency along with fourteen crisis events. Eighteen chapters are focused on one crisis event while ten chapters directly or indirectly engage poly-crises. As crises and polycrises become a constancy of our time, this volume will be of great interest to students, researchers, and practitioners of public administration and public policy"-- Provided by publisher.
Keywords: Crisis management in government.; Communication in crisis management.; Crisis management -- Technological innovations.; COVID-19 Pandemic, 2020-2023 -- Government policy.; elektronické knihy; electronic books